USES OF THE FIRST LANGUAGE IN THE ENGLISH AS A FOREIGN/SECOND LANGUAGE CLASSROOM: TEACHERS’ VIEWS AND ARGUMENTS - Luitel, Binod; Poudel, Kamal Kumar; Sharma, Uma Nath; Karki, Tek Mani (TEFLIN Journal, 2023)
Drawing on the lived experiences of three community school English teachers in Nepal, this article explores the uses of the learners’ first language (L1) in English as a foreign/second language (ESL) classes. As the data, we collected the written lived-experience descriptions from the teachers, observed their classes, and interviewed them. We analyzed the data thematically and interpreted them contextually. As the study found, the teachers have their lived experiences of using the L1 for its cognitive roles – namely, for checking learners’ understanding, facilitating them in task performance, and increasing understanding on the part of the students in various aspects of language learning – including content, vocabulary, grammar, stories, poems, and cultural concepts. Drawing on the teachers’ convictions, we have advanced that the L1 (here, Nepali) does play the role of cognitive bridging in English language learning, particularly when the students have a ‘poor English base’ (as perceived by the participants in this study), and when both the teacher and the students share a common L1. Hence, the general implication could be that the L1 can function as a support in teaching and learning a second/foreign language (L2).